PENERAPAN MODEL QUANTUM LEARNIG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VB SDN 12 AIR JAMBAN KECAMATAN MANDAU KABUPATEN BENGKALIS - Kamilia, Kamilia; Hamizi, Hamizi; Erlisnawati, Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :The problem this research is the student achievement of Mathimatic studies fifth graderes SDN 12 Air Jamban Kecamatan Mandau Kabupaten Bengkalis still low with an average value of 53,12 and minimum completenness criteria (KKM) mathematic studies is 65. Between students, amounting to 32 people only 13 students who achieve classical KKM with 40%. This research is Classroom action Research (CAR), wich aims to improve the learning process in the classroom. Formulation of the problem : is the implementation quantum learning can improve students achievment of mathematic studies at SDN 12 Air Jamban Kecamatan Mandau Kabupaten Bengkalis. The research was conducted on march 16, 2015 to april 01, 2015 by 2 cyclees. Subjects were students of SDN 12 Air Jamban Kecamatan Mandau Kabupaten Bengkalis, totalling 32 people who use the data source. The data collection instruments in this research is a teacher and students activities sheets and students achievement. Based on the achievement research of activity the teacher in the lerning process in cycle I frist meeting was 75% and at the second meeting of teacher activity increased to 83%. cycle II firs meeting and the second meeting of activity increased to 90% and the second meeting of activity increased to 96%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an avarage of 70,8% and at second meeting of activity increased to 75% and a second meeting of activity increased improve to 88%. At the firs meeting of the second meeting of activity increased to 96%.This research presents the results obtained each before the implementation an improve in base score sycle with the average being, 53,12. In the first cycle improve an average of 71 with increase as 33,64% and an impove in the second with an average of 84,25 with increase as 58,58%. Result in the research that the implementation of quantum learning can improve students achievement of mathematic Studies at fifth graderes SDN 12 Air Jamban Kecamatan Mandau Kabupaten Bengkalis.Key Words : Model Quantum Learning, Mathematic student’s achievement